Human papillomavirus (HPV) infection and vaccination - Troha, Majda (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2018)
Introduction: This study evaluates knowledge of and attitudes toward human papillomavirus (HPV) infection and vaccination among healthcare professionals and the general public in Slovenia. Methods: Five statements were designed to evaluate participants' opinions regarding age at HPV vaccine administration and potential delay in vaccination, associations of HPV vaccination with riskier sexual behavior, HPV vaccine safety, the importance of the internet as a source of information, and the significance of HPV vaccination in boys. Participants were asked to express agreement or disagreement with each statement. Results: A total of 605 surveys were completed by medical students (n = 259), parents of sixth-graders in 2016 (n = 103) and 2017 (n = 103), pediatricians and school medicine specialists (n = 21), gynecologists (n = 34), and women visiting gynecology outpatient clinics (n = 85). The highest level of knowledge and belief in the HPV vaccine and its safety was observed among pediatricians and school medicine specialists. Medical students tend to have a very positive attitude toward HPV vaccination, although they need additional education about HPV vaccine safety. Some healthcare professionals showed signs of HPV vaccine hesitancy, and their beliefs were somewhat similar to those of the general public. Conclusions: Although the overall attitude towards HPV vaccination is generally positive, additional education must be provided to both healthcare professionals and the general public in order to achieve higher HPV vaccination coverage rates in Slovenia.
Keywords: cepljenje proti HPV; general public; healthcare professionals; HPV vaccination; splošna javnost; zdravstveni delavci